The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.5433/1679-0359.2017v38n6p3739
|View full text |Cite
|
Sign up to set email alerts
|

Age castration of Nellore males on the profile of fatty acids of meat

Abstract: This study aimed to evaluate the cholesterol content, α-tocopherol and fatty acids in the meat of Nellore young bulls or steers castrated at different ages, 13 or 18 months. The animals were confined for 100 days and slaughtered at 22 months of age. The experimental design was completely randomized with three treatments, using 12 repetitions. The levels of palmitic acid (26.39%), stearic (24.39%), myristic (3.01%) and total saturated fatty acids were not altered by sexual condition or castration age. Oleic was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
2
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 25 publications
1
2
0
4
Order By: Relevance
“…The predominant unsaturated fatty acid in both Bali and Wagyu beef was oleic acid (C18:1n9c). This study was aligned with previous research that has consistently identified oleic acid (C18:1n9c) as having the highest concentration among unsaturated fatty acids (Missio et al, 2017;Fiorentini et al, 2018). The results showed that the average content of oleic acid (C18:1n9c) in Bali beef was lower than in Wagyu beef but higher than the results of Bain et al (2016) for Bali cattle (6.30%) with a diet consisting of fed 40% grass and 60% concentrate.…”
Section: Fatty Acid Profile In Different Breedssupporting
confidence: 89%
“…The predominant unsaturated fatty acid in both Bali and Wagyu beef was oleic acid (C18:1n9c). This study was aligned with previous research that has consistently identified oleic acid (C18:1n9c) as having the highest concentration among unsaturated fatty acids (Missio et al, 2017;Fiorentini et al, 2018). The results showed that the average content of oleic acid (C18:1n9c) in Bali beef was lower than in Wagyu beef but higher than the results of Bain et al (2016) for Bali cattle (6.30%) with a diet consisting of fed 40% grass and 60% concentrate.…”
Section: Fatty Acid Profile In Different Breedssupporting
confidence: 89%
“…Em alguns dos principais países produtores de carne bovina o uso de substâncias anabolizantes, de natureza hormonal ou não, tem sido difundida como alternativa para aumentar a produção (FERRÃO & BRESSAN, 2006, MISSIO et al, 2017. Cabe salientar que no Brasil é proibido o uso dessas substâncias (CARDOSO et al, 1999).…”
Section: Introductionunclassified
“…Nesse contexto a produção de carne a partir de machos inteiros apresenta boa aceitação entre os produtores, principalmente pelo fato de exigir pouco investimento de capital (RESTLE et al, 1999;MISSIO et al, 2017) e não ser considerado uma prática ilegal.…”
Section: Introductionunclassified
See 1 more Smart Citation
“…Além disso, a carne produzida por animais inteiros possui características semelhantes a dos animais castrados, quando abatidos em idades reduzidas (RODRIGUES SILVA et al, 2004;MISSIO et al, 2017). A utilização desta alternativa vem crescendo nos últimos anos, principalmente no centro-oeste do país, onde a prática da castração está diminuindo nos sistemas produtivos.…”
Section: Introductionunclassified